2022
DOI: 10.3390/biology11030443
|View full text |Cite
|
Sign up to set email alerts
|

Atrial High-Rate Episodes Detected by Cardiac Implantable Electronic Devices: Dynamic Changes in Episodes and Predictors of Incident Atrial Fibrillation

Abstract: Background. Atrial high rate episodes (AHRE) detected by cardiac implantable electronic devices (CIEDs) may be associated with a risk of progression towards long-lasting episodes (≥24 h) and clinical atrial fibrillation (AF). Methods. Consecutive CIED patients presenting AHRE (with confirmation of an arrhythmia lasting 5 min–23 h 59 min, atrial rate ≥175/min, with no AF at 12-lead ECG and no prior clinical AF) were retrospectively enrolled. The aims of this study were to describe patients’ characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…It can be speculated that the lack of significant improvement in LA function in the AF cohort may be due to a higher degree of atrial cardiomyopathy, which prevented reverse remodeling. Indeed, AF promotes and sustains a vicious circle of atrial electrical and structural remodeling, possibly leading to "domestication" of the arrythmia and derangement in atrial volumes, geometry, function, and cellular structure [27][28][29]. Furthermore, the small sample size and the high number of patients in AF at baseline compared to previous studies could explain the limited extent of reverse remodeling [26].…”
Section: Left Ventricular and Atrial Chambers Remodelingmentioning
confidence: 98%
“…It can be speculated that the lack of significant improvement in LA function in the AF cohort may be due to a higher degree of atrial cardiomyopathy, which prevented reverse remodeling. Indeed, AF promotes and sustains a vicious circle of atrial electrical and structural remodeling, possibly leading to "domestication" of the arrythmia and derangement in atrial volumes, geometry, function, and cellular structure [27][28][29]. Furthermore, the small sample size and the high number of patients in AF at baseline compared to previous studies could explain the limited extent of reverse remodeling [26].…”
Section: Left Ventricular and Atrial Chambers Remodelingmentioning
confidence: 98%
“…It suggested that the duration of AHRE determined the risk of thromboembolism more than the numbers of the AHRE. 11 There was a study showing that the risk of thromboembolic events was less than 1% in the patients with AF duration of less than 48 h. 21 The length of AF duration associated with the stroke risk. 22 factors with an AHRE burden > 5.5 h/day for stroke prevention.…”
Section: Relationship Between Ahre Duration and Ischemic Strokementioning
confidence: 99%
“…Cardiac implanted electronic device (CIED) can monitor fully quantified atrial high‐rate episode (AHRE). There are a lot of evidence to prove that AHRE represent the occurrence of AF 7–14 . Studies have shown a two‐fold increased risk of thrombotic events in patients with AHRE detected by CIEDs 6,8 .…”
Section: Introductionmentioning
confidence: 99%
“…This may vary and range from the duration of monitoring with telemetry, execution of 12-lead ECG at standardized time intervals after surgery, up to the planning of intermittent Holter recordings, or even continuous monitoring through implanted devices, further enhanced by remote monitoring functions [11]. In the latter context, indeed, it is known that episodes of atrial tachyarrhythmia lasting a few minutes are commonly detected by cardiac implantable electronic devices and may progress to clinical AF in up to 30% of patients at 2-year follow-up [12,13]. Since AF is strictly linked to a variety of factors (Figure 1), such as patients' age and a variable combination of cardiac substrate, triggers, precipitating factors, and altered autonomic modulation, it appears that, in this context, individualized decision-making is needed also with regard to indication for long-term OAC and extent of monitoring for patients in whom anticoagulation is not established or is prescribed for a limited period after surgery [14].…”
Section: Related Articlementioning
confidence: 99%